Genome-wide association for multiple quantitative traits in forage oat germplasm based on specific length amplified fragment sequencing - Li, Yue; Zhu, Kai; Cui, Huiting; Hu, Qiannan; Wang, Chu; Jia, Fang; Kang, Junmei; Ma, Chengze; Sun, Yan (Frontiers in Plant Science, 2025)
Oats (Avena sativa L.) is an ideal forage species due to its excellent production performance, high nutritional value, and robust adaptability. In the present study, we analyzed plant height (PH), panicle length (PL), stem diameter (SD), node number (NN), flag leaf length (FLL), flag leaf width (FLW), second leaf length (SLL), and second leaf width (SLW) in a collection containing 340 forage oat accessions, in order to perform a genome-wide association study (GWAS) for identifying markers associated with the eight traits. We genotyped this collection using specific length amplified fragment sequencing (SLAF-seq). Phenotypes for PH, PL, SD, NN, FLL, FLW, SLL, and SLW were collected under natural conditions in four environments. GWAS analyses detected six significant associations for NN and three for FLL. Candidate genes of the nine associations were screened and discussed. Several genes were found to be associated with node number, including zinc finger MYM-type protein 1-like isoform X1, ervatamin-B-like, Pimeloyl-ACP methyl ester carboxylesterase, and ACT domain-containing protein ACR4-like, involved in cell division and organ development. Additionally, three genes were linked to flag leaf length—putative aquaporin PIP2-2, triacylglycerol lipase OBL1-like, and scarecrow-like protein 21—involved in the regulation of plant development and stress response. These SNP markers may be useful to accelerate the breeding progress of forage oat in temperate monsoon environments.